Further integration with the EU: Just one ingredient in the reform process - Armin Riess; Patrick Vanhoudt; Kristian Uppenberg (EIB Papers, 2001)
This paper provides a broad survey of the economic situation in nine Mediterranean Partner Countries, and assesses the impact of the Euro-Mediterranean association agreements. The starting point of the analysis is the observation that overall economic performance of the region has been relatively poor when measured as growth of income per capita. Several factors are likely to have contributed to this. Investment in physical and human capital has both been lower and less efficient than in more successful developing economies. In addition, inward-looking development strategies have been combined with extensive state ownership and overall involvement in the economies to produce a high degree of protection. This has hampered competition and limited the gains from trade, leading to low productivity growth. In light of this experience, it is argued that the Euro-Mediterranean trade agreements are a necessary but not a sufficient element in bringing the region onto a more promising path of economic development. The freeing-up of trade with the EU needs to be accompanied by domestic economic reforms on a broad scale to facilitate needed structural transformation and to reduce the fiscal dependency on tariffs. Similarly, the Mediterranean countries need to remove trade barriers also between each other, so as to create a sufficiently large regional market to attract the foreign direct investment necessary to modernise their economies.
Keywords: 330; Wirtschaftslage; Wirtschaftsreform; Steueraufkommen; Direktinvestition; Nordafrika; Mittlerer Osten